2018
DOI: 10.1248/bpb.b18-00349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplementary Seleno-L-methionine on Atopic Dermatitis-Like Skin Lesions in Mice

Abstract: Effects of selenium supplementation on atopic dermatitis (AD) were investigated by administering seleno-L-methionine (SeMet) using a mouse model of AD caused by repeated application of 2,4,6-trinitrochlorobenzene (TNCB). BALB/c mice were sensitized with TNCB to the abdomen on day -7; then, TNCB was applied repeatedly to each ear three times a week from days 0 to 23. SeMet was orally administered to the mice from days 0 to 23. The efficacy of SeMet on AD was assessed by measuring ear thickness, histologic evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…However, this remains speculative as we did not measure B-cell activation markers. In a murine model for atopic dermatitis, oral administration of Se suppressed the development of atopic dermatitis-like skin lesions, lowered total IgE levels, reduced skin expression of IL-4 and led to a lower number of mast cells in the skin [ 36 ]. In our current study, we observed a significantly lower expression of serum mMCP-1 in mice that were fed the high Se diet, suggesting that mast cells may be affected also by this dietary intervention with Se.…”
Section: Discussionmentioning
confidence: 99%
“…However, this remains speculative as we did not measure B-cell activation markers. In a murine model for atopic dermatitis, oral administration of Se suppressed the development of atopic dermatitis-like skin lesions, lowered total IgE levels, reduced skin expression of IL-4 and led to a lower number of mast cells in the skin [ 36 ]. In our current study, we observed a significantly lower expression of serum mMCP-1 in mice that were fed the high Se diet, suggesting that mast cells may be affected also by this dietary intervention with Se.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the latter suggested urushiol-mediated immunogenic mechanisms, isolated CD8+ T cells from skin lesions of urushiol sensitized human subjects favor their role in the effector phase of contact dermatitis produced by poison ivy (Kalish and Johnson, 1990). Current studies indicate that IL-4 is an important downregulator during the elicitation phase of contact sensitivity (CS), demonstrated by the presence of high levels of IL-4 mRNA in the dermis and epidermis following skin challenge with trinitrochlorobenzene (TNCB) (Asada et al, 1997; Arakawa et al, 2018). Also, mice treated with anti-IL-4 mAb shortly before ear challenge showed increased ear swelling responses, this being accompanied by enhanced IFNγ, IL-2, and IL-12 mRNA signals in the dermis.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium substitutions of L-Methionine are known as L-Selenomethionine or L-Selenoneine. These amino acids have high antioxidant activities, and L-Selenomethionine can suppress allergic dermatitis 11 . Thus, the high value for L-Methionine was likely due to the existence of L-Selenomethionine and L-Selenoneine.…”
Section: Analysis Of Amino Acids By Uhplcmentioning
confidence: 99%